Molecular markers for breast cancer diagnosis, prognosis and targeted therapy. Issue 1 (5th August 2014) - Lang, Julie E.; Wecsler, Julie S.; Press, Michael F.; Tripathy, Debasish
<x xml:space="preserve">Abstract</x> Precision medicine involves understanding the molecular drivers unique to an individual patient's cancer so that specific factors may be targeted with the goal of improved patient outcomes. The purpose of this article is to review standard of care and research grade (non‐standard of care) biomarkers in breast cancer that may be useful for diagnosis, prognosis and targeted therapy. J. Surg. Oncol. 2015 111:81–90. © 2014 Wiley Periodicals, Inc.